2004
DOI: 10.1186/1471-2091-5-8
|View full text |Cite
|
Sign up to set email alerts
|

The VSFASSQQ motif confers calcium sensitivity to the intracellular apyrase LALP70

Abstract: BackgroundApyrases are divalent ion dependent tri- and dinucleotide phosphatases with different substrate specificity. The intracellular lysosomal apyrase LALP70 is also expressed as a splice variant (LALP70v) lacking a VSFASSQQ motif in the center of the molecule (aminoacids 287–294). However, the functional significance of this motif is unknown. In this report we used a thin layer chromatography approach to study separately the UTPase and UDPase activity of the two LALP-enzymes.ResultsWe show, that LALP70 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…MDC has been described as a specific autophagic vacuole marker (Biederbick et al, 1995), but since this compound also acts as a lysosomotropic agent, MDC could eventually label some acidic compartments derived form the endocytic pathway. Therefore, we used monodansylpentane (MDH) that is a new derivative of MDC (Niemann et al, 2001).…”
Section: Autophagic Vacuoles Are Decorated By Egfp-rab7mentioning
confidence: 99%
See 2 more Smart Citations
“…MDC has been described as a specific autophagic vacuole marker (Biederbick et al, 1995), but since this compound also acts as a lysosomotropic agent, MDC could eventually label some acidic compartments derived form the endocytic pathway. Therefore, we used monodansylpentane (MDH) that is a new derivative of MDC (Niemann et al, 2001).…”
Section: Autophagic Vacuoles Are Decorated By Egfp-rab7mentioning
confidence: 99%
“…For this purpose we generated stably transfected CHO cells that overexpress the chimeric proteins EGFP-Rab7 wt and the mutants Q67L and T22N. Autophagic vacuoles were labeled with the autofluorescent drug monodansylcadaverine (MDC), a specific autophagosomal marker (Biederbick et al, 1995;Munafo and Colombo, 2001). By fluorescence microscopy we observed that, in living cells transfected with pEGFP-Rab7 wt and the active mutant Rab7Q67L (Fig.…”
Section: Autophagic Vacuoles Are Decorated By Egfp-rab7mentioning
confidence: 99%
See 1 more Smart Citation
“…7). To determine whether these vacuoles were autophagic vacuoles, infected cells were labelled with an autofluorescent drug, MDC, a selective marker for autophagic vacuoles (Biederbick et al, 1995). MDC-labelled vesicles were not evident in HeLa cells infected with wild-type (Fig.…”
Section: Parahaemolyticus Does Not Induce Autophagy In Hela Cellsmentioning
confidence: 99%
“…The LALP70 mRNA contains an additional stretch of 24 bp, which encodes 8 amino acids inserted in-frame into the UDPase protein sequence (30)(31)(32). This additional 8-residue motif was reported to confer calcium sensitivity to LALP70 (33), and the apyrase products of the two splice variants were shown to possess somewhat different enzymatic properties (30). The two NTPDASE4-encoded proteins differ also in their reported cellular localization.…”
mentioning
confidence: 99%